2017
DOI: 10.1007/s40520-017-0869-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of long-term care among nonagenarians: the Vitality 90 + Study with linked data of the care registers

Abstract: Risk of entering into LTC was increased among women, subjects with at least two chronic conditions, those living alone and with higher level of received help. Since number of nonagenarians will increase and the need of care thereby, it is essential to understand predictors of LTC entry to offer appropriate care for the oldest old in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
12
0
5
Order By: Relevance
“…Studies have also found that MetS is significantly related to the ADL and IADL of the elderly living in the community [ 53 , 54 , 55 ]. However, other studies have shown that MetS is associated with mobility restrictions but not related to the disability of ADL or IADL in older Mexican Americans [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found that MetS is significantly related to the ADL and IADL of the elderly living in the community [ 53 , 54 , 55 ]. However, other studies have shown that MetS is associated with mobility restrictions but not related to the disability of ADL or IADL in older Mexican Americans [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several definitions are proposed: the American Geriatric Society and the World Health Organization define the oldest old as individuals aged over 80 years, while the British Geriatrics Society uses 85 years as a threshold. In recent publications, the cut off has been fixed at 85 or 90 years and over [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increasing number of cohorts studied in order to describe this population, such as the 90+ study, the Leiden 85-plus study, the Vitality 90+ study, the Newcastle 85+ study [e.g. [7][8][9][10], or recent literature on centenarians [13][14][15], few data describe the global status of individuals aged 90 and over.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies indicated that caregivers' burden was a predictor of institutionalization [34][35][36]. Severe incontinence may exceed the potential of informal care and Kauppi et al [37] have reported that partial assistance provided for older person (i.e., covering only part of the gap to reduce but not eliminate the excessive burden) was a predictor of institutionalization. The knowledge of health services also influenced LTC choices, particularly in the case of severe incontinence.…”
Section: Discussionmentioning
confidence: 99%